Juvenile Nasopharyngeal Angiofibroma Presenting with Acute Airway Obstruction - Chikoti Wheat; Ryan J. Bickley; Erik Cohen; Danya Wenzler; Nancy Hunter; Donna Astiz (Case Reports in Otolaryngology)
We describe a case of a 24-year-old male presenting urgently with a juvenile nasopharyngeal angiofibroma (JNA) with difficulty breathing, inability to swallow, and respiratory distress following throat swelling. The swelling was reduced with administration of dexamethasone and the JNA was surgically resected within 48 hours. This presentation was atypical given the acuity of presentation and the patient’s older age.